Pengembangan Permainan Edukasi Simulasi Astronomi Menggunakan Teknologi Mobile Virtual Reality - Firly Wahyudi; Wibisono Sukmo Wardhono; Amminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Virtual Reality Technology in this era could be implemented toward every aspect in life. One of those aspect is Education. The implementation of this technology in education field has a goal to increase the student reception toward information. Virtual Reality implementation with head mounted display on an android platform can increase student reception toward information by stimulating student's senses through those technology. Another positif effect by using both of those technology can make the game more interactive, intuitive and fun. The development process begins with planning and evaluation. The design process is done by determining the formal elements in the game, determining the rules, goals and so on. The elements will work as a whole to form a game in accordance with the design. The process will continue at the digital stage of prototyping and evaluation. The prototyping stage will illustrate the initial draft that will describe the game as a whole. The prototypes will be evaluated for their feasibility to be implemented. From the results of implementation on the development, will be tested that will measure the feasibility of the system that has been developed